Role of Sex Hormones in the Development and Progression of Hepatitis B Virus-Associated Hepatocellular Carcinoma - Maurizio Montella; Giovanni D’Arena; Anna Crispo; Mario Capunzo; Flavia Nocerino; Maria Grimaldi; Antonio Barbieri; Anna Maria D’Ursi; Mario Felice Tecce; Alfonso Amore; Massimiliano Galdiero; Gennaro Ciliberto; et al. (International Journal of Endocrinology)
Infection with hepatitis B virus (HBV) is a major risk factor for hepatocellular carcinoma (HCC) in developed countries. Epidemiological reports indicate that the incidence of HBV-related HCC is higher in males and postmenopausal females than other females. Increasing evidence suggests that sex hormones such as androgens and estrogens play an important role in the progression of an HBV infection and in the development of HBV-related HCC. While androgen is supposed to stimulate the androgen signaling pathway and cooperate to the increased transcription and replication of HBV genes, estrogen may play a protecting role against the progression of HBV infections and in the development of HBV-related HCC through decreasing HBV RNA transcription and inflammatory cytokines levels. Additionally, sex hormones can also affect HBV-related hepatocarcinogenesis by inducing epigenetic changes such as the regulation of mRNA levels by microRNAs (miRNAs), DNA methylation, and histone modification in liver tissue. This review describes the molecular mechanisms underlying the gender disparity in HBV-related HCC with the aim of improving the understanding of key factors underneath the sex disparity often observed in HBV infections. Furthermore, the review will propose more effective prevention strategies and treatments of HBV-derived diseases.